Rancang Bangun Aplikasi Pencarian Bengkel Dan Cuci Motor Terdekat Berbasis Mobile - Liza Yuliana Khairani; Ario Yudo Husodo; Fitri Bimantoro (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
As the number of motorcycles users are increasing in Indonesia, so is the problems of the motorcycles that they face. On the other hand, the user of the smartphone is increasing as well. Based on that matters, we can develop an application in order to help the user to cope with their problem easier. The application can help the user to find the nearest garage and motorcycles wash, in order to solve the problems, such as dirty motorcycle, flat tire, the tire burst, oil change, etc. This application was designed to provide some information about the nearest garage, the route to the garage, reveal the comments and send a message to the owner of the garage. Meanwhile, the owner of the garage can see the comments about their garage, receive an order and see the customer location. The testing technique which was used in this research were blackbox and MOS testing. The result of blackbox testing showed that all features can be run as planned, meanwhile, the MOS testing showed the customer respondents value was 84,83% and the owner respondents value was 84,77%. Keywords: Garage location, Motorcycles, Problems of the Motorcycles, Order Service, MOS Testing.